Study on the Advertising Insertion Forms in the Creativity of Online Variety Programs: Taking "Back to Field" as an Example - Zhang, Tingxuan (Transactions on Social Science, Education and Humanities Research, 2023)
With the arrival of the The Internet Age, the information dissemination environment and the needs of the audience have undergone tremendous changes. The advertising market in China has undergone significant changes from the 20th century to the 21st century, with significant changes in form, from traditional media advertising to new media and internet advertising. With the increase of media forms, the saturation of the current traditional advertising market is relatively high, and the choices of advertisers are limited. Therefore, various platforms and media embedded advertising have begun to be sought after by advertisers. The audience’s tolerance for repetitive and vulgar placement advertisements is decreasing, and placement advertisements have emerged as the times require. Placement advertisements have the characteristics of diverse advertising forms, being able to leave a deep impression on the audience, and having a good impression on the audience. The emergence of slow variety shows has provided new opportunities for advertising placement and has been favored by many advertisers. Variety shows are in a rapid development stage, and advertising placement, as one of their development assistance, is also constantly developing, and in the process of development, more new advertising placement models are constantly being applied. This article takes "Back to Field" as an example to analyze the advertising insertion forms in the creativity of online variety shows.